Estrogen receptor mutations and functional consequences for breast cancer. (September 2015) - Thomas, Christoforos; Gustafsson, Jan-Åke
Highlights There is a substantial frequency of ESR1 point mutations in metastatic breast tumors. ESR1 mutations are implicated in clinical resistance to hormonal therapy. ESR1 mutations render receptor activity constitutive by altering receptor conformation. Early detection of the mutations can guide proper selection of therapy. Novel therapeutics to overcome resistance conferred by the mutations are being tested.